Abatement techniques for reducing emissions from livestock buildings - Samer, Mohamed (Switzerland : Springer, 2016)
This book identifies future scientific research priorities for developing emissions inventories, emissions abatement techniques and mitigation strategies in order to improve and sustain livestock production that is in line with climate change adaptation. Livestock production is a major source of atmospheric pollutants and greenhouse gases, such as methane, nitrogen oxides, carbon dioxide and ammonia, all of which directly contribute to global warming and climate change. Air pollutant emissions from agricultural practices have a negative environmental impact and are of relevant political importance, as highlighted in both the Kyoto and Gothenburg Protocols. This book provides solutions on how to abate these emissions by using effective abatement techniques such as additives, manure storage covers, aerobic and anaerobic treatments, and dietary manipulation. Each chapter in the book provides valuable, up-to-date information on abatement techniques, thus allowing the reader to better understand the issues involved. Recent advances and new perspectives in the field are also discussed.
Keywords: MITIGACION DEL DIOXIDO DE CARBONO; METANO; GASES DE EFECTO INVERNADERO